Stress responses of transportation on red tilapia which given feed containing chromium - Rakhmawati, Rakhmawati; Muhammad Agus Suprayudi; Mia Setiawati; Widanarni, Widanarni; Muhammad Zairin Junior; Dedi Jusadi (Jurnal Akuakultur Indonesia)
ABSTRACT This study was conducted to evaluate stress responses of transportation on red tilapia Oreochromis sp. which given feed containing chromium. Three isonitrogenous and isocaloric experimental feeds were prepared, these diets were control (without chromium), CrPic 1 mg/kg, and CrYst 2 mg/kg supplementation in feed, all group were arranged triplicate. Satiation feeding was done three times a day. After a 60-day feeding experiment, the experimental fishes were fasted and distributed in polyethylene bags (N=60 fish/bag) containing 3 L of water, subjected to condition of transport simulation for 13 hours. Survival rate, levels of plasma cortisol, blood glucose, superoxide dismutase (SOD), and malondialdehyde (MDA) enzyme were observed at before transportation, after transportation, one day, and two days after transportation. The result showed that chromium supplementation reduced the levels of plasma cortisol before and after transportation, one day, and two days after transportation. Also, it decreased blood glucose compared with control significantly before transportation and one day after transportation. The SOD enzyme concentration increased significantly after fish was fed with feed containing chromium for 30 days, while the MDA enzyme concentration increased significantly after two days of transportation. However, there was no significant difference in the survival of red tilapia between treatments. The best result was obtained in the treatment of fish which fed with feed containing chromium. CrPic supplementation 1 mg/kg and CrYst 2 mg/kg increased the body resistance in red tilapia by decreasing the negative effect of stress while transportation.